The Story for children : a storybook Bible - Lucado, Max.; Hill, Karen, 1947-; Frazee, Randy; Bianchi, Fausto (Grand Rapids, Mich. : Zonderkidz, 2011)
Presents forty-eight brief Bible stories from the Old and New Testaments, from the Creation to the second coming of Jesus, along with an explanation of each one's meaning.
Keywords: Bible stories, English; Bible stories, English -- Juvenile literature; Bible stories; Bible stories